Quantitative analyses of the main che mical constituents in the roots of Echinacea purpurea and E. angustifolia produced in Cos ta Rica - Loaiza, Jorge (2004)
Free phenylpropanoids (chlorogenic and cichoric acids), and a glycosidic (echinecoside), as well as the alkamides, present in root extracts of the medicinal plants Echinacea purpurea and E. angustifolia produced in 3 different locations of Costa Rica (Los Santos at 1650 masl, Santa Bárbara de Heredia at 1250 masl and Ojo de Agua at 850 masl) were quantified. Results showed a decrease on secondary metabolites associated to an altitude reduction of the growing zone. Concentration of free phenylpropanoids and the echinecoside (produced exclusively for E. angustifolia) were 100 and 34 % higher than the concentration reported for a standard sample from U.S.A. Alkamides concentration ranged from 0.89-2.31%, as compared to 0.004-0.36% reported from U.S.A. The alkamides produced in Costa Rica were similar in the 3 growing zones. In addition, 2 of them showed different isomerism than the ones reported in samples from U.S.A. These results indicate that in tropical conditions not only is it possible to produce Echinacea, but also that the amount of metabolites is higher than those produced in the Echinacea’s origin areas. The presence of compounds with different isomerism could provide an alter native use for those metabolites.